A triumph of realism? Britain, Aden and the end of empire, 1964–67. Issue 1 (2nd January 2017) - Edwards, Aaron
ABSTRACT: The Labour Government's decision to withdraw from Britain's overseas bases east of Suez in the 1960s had profound repercussions for British grand strategy. One of the last colonies to be evacuated was the port town of Aden, located on the south-western tip of the Arabian Peninsula. First seized by the East India Company on behalf of the British Empire in 1839, it became a Crown Colony almost a century later in 1937. By 1963, the British government had presided over Aden's entry into the fledgling Federation of South Arabia, a transitional body that was envisaged as a vehicle for independence. Drawing on the Labour's Party's archives, amongst a range of other sources, this article examines the shift in policy within the Labour government on the issue of Aden. It makes the case that, in contrast to the Conservative government's wholehearted support for Britain's tribal allies in South Arabia, Labour hedged its bets by balancing its policy off between the tribal rulers and the new radical nationalist opposition. By refusing to back the fledgling Federation government, Labour, instead, adopted a non-committal stance that would lead to greater strategic inertia in its policy towards the Middle East during the Cold War.